2023
DOI: 10.21203/rs.3.rs-3156608/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Out-of-hospital cardiac arrest in children: An epidemiological study based on the German Resuscitation Registry identifying modifiable factors for return of spontaneous circulation

Abstract: Aim This work provides an epidemiological overview of out-of-hospital cardiac arrest (OHCA) in children in Germany between 2007 and 2021. We wanted to identify modifiable factors associated with survival. Methods Data from the German Resuscitation Registry (GRR) was used, and we included patients registered between 1st January 2007 and 31st December 2021. We included children aged > 7 days and < 18 years, where cardiopulmonary resuscitation (CPR) was started and treatment was continued by emergency med… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In two population-based registry studies of children aged 0-17, the authors found similarly low incidences of cardiac arrest [6]. The studies also showed diversity in causes, contrasting with the adult population where cardiac causes predominate.…”
mentioning
confidence: 92%
“…In two population-based registry studies of children aged 0-17, the authors found similarly low incidences of cardiac arrest [6]. The studies also showed diversity in causes, contrasting with the adult population where cardiac causes predominate.…”
mentioning
confidence: 92%